Child safety car reverse parking system / Ida Rahayu Mohamed Noordin ... [et al.] - Mohamed Noordin, Ida Rahayu; Ainur Elleshahani Zulkifli, Rohaiza; Baharudin, Rohaiza; Abdul Razak, Siti Nabilah (College of Built Environment, 2023)
Every year, thousands of children are killed or seriously injured because a driver backing up didn't see them.